Construction of comprehensive evaluation model of the CPA multi-criteria decision-making for charging pile location. (8th October 2022) - Chen, Zixia; Meng, Wang; Zeng, Fanlong; Zhu, Hanmin
Based on the advantages of subjective and objective weighting methods, this paper constructs a combination optimisation weighting model of G1-CRITIC to solve the multi-criteria decision-making problem of electric vehicle charging pile. The solution process is a comprehensive evaluation process based on the combination of the G1 algorithm of probability language, the Entropy Weight algorithm and the CPA algorithm. In order to validate the applicability of the proposed charging pile location decision-making model, which is based on the construction of the location index system, this paper uses the MATLAB software to generate the simulation data for four alternative location problems. Relevant experts are invited to adopt the comprehensive evaluation method designed in this paper is used to make a decision on the location of electric vehicle charging pile. The results of this study show that the decision-making method can obviously improve the decision-making level of multi-criteria decision-making problems.